Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have no clue how to proceed with this question. Please help me in deriving the differential equations! Thanks very much... I really appreciate it :)

enter image description here

share|cite|improve this question
up vote 4 down vote accepted

Complete derivation of the differential equations. [Suggestion: After each step below, try completing the derivation on your own.]

$$ P_0 (t + h) = {\rm P}(N(t + h)\;{\rm is} \; {\rm even}|N(t)\;{\rm is} \; {\rm even})P_0 (t) + {\rm P}(N(t + h)\;{\rm is} \; {\rm even}|N(t)\;{\rm is} \; {\rm odd})P_1 (t). $$ Put $\Delta_t(h) = N(t+h)-N(t)$. Then, as $h \downarrow 0$, $$ P_0 (t + h) = {\rm P}(\Delta_t(h)=0|N(t)\;{\rm is} \; {\rm even})P_0 (t) + {\rm P}(\Delta_t(h)=1|N(t)\;{\rm is} \; {\rm odd})P_1 (t) + o(h). $$ Hence, $$ P_0 (t + h) = [1 - {\rm P}(\Delta_t(h)=1|N(t)\;{\rm is} \; {\rm even})]P_0 (t) + {\rm P}(\Delta_t(h)=1|N(t)\;{\rm is} \; {\rm odd})P_1 (t) + o(h), $$ leading to $$ P_0 (t + h) = (1-\beta h)P_0 (t) + \alpha h P_1 (t) + o(h). $$ Rearranging gives $$ \frac{{P_0 (t + h) - P_0 (t)}}{h} = \alpha P_1 (t) - \beta P_0 (t) + \frac{{o(h)}}{h}. $$ Letting $h \downarrow 0$ thus gives $$ P'_0 (t) = \alpha P_1 (t) - \beta P_0 (t) . $$ Similarly, $$ P'_1 (t) = \beta P_0 (t) - \alpha P_1 (t) , $$ which also follows trivially from $P_0 (t) + P_1 (t) = 1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.